Effect of magnetic nanoparticles on the morphology of polystyrene-b-poly(methyl methacrylate) diblock copolymer thin film - Yang, Ping (2013)
We report the effect of oleic acid-capped magnetic nanoparticles (mNPs, γ-Fe2O3) on the morphology and phase separation behavior of diblock copolymer thin film, polystyrene-b-poly(methyl methacrylate), PS-b-PMMA, under various experimental conditions such as the casting solvent, mNPs concentration, and the annealing time. If chloroform (CHCl3, slightly selective for PMMA) is selected as the casting solvent, the morphologies of the PS-b-PMMA thin film are affected by the embedded mNPs, while there will be no such effect when toluene (slightly selective for PS) is used. In toluene systems, at lower mNP concentration, lateral microphase separation occurred faster than that without mNPs, but at higher concentration, the underlying self-assembled diblock copolymer structure is no longer correlated with the mNPs assembly. Increasing the annealing time of the PS-b-PMMA/mNPs nanocomposite thin film causes a similar effect as that of increasing the concentration of mNPs.